Mothers’ Gratitude and Psychological Well-Being in Raising Children with Autism in Indonesia: A Meta-Analysis - Henny Puji Astuti; Dewi Retno Suminar; Primatia Yogi Wulandari; Pramesti Pradna Paramita; Cholichul Hadi; Nur Ainy Fardana; Nono Hery Yoenanto; Fitri Andriani (Jurnal Kesehatan Masyarakat, 2026)
Education is a fundamental right for all children, both within schools and in the family environment. The psychological well-being of mothers plays a crucial role in raising children with autism. Various factors contribute to the formation of maternal psychological well-being, one of which is gratitude. This study aims to examine the correlation effect size between gratitude and mothers’ psychological well-being in raising children with autism. A meta-analysis was conducted on seven research articles and two research reports identified through Google Scholar, Portal Garuda, and Indonesia ONESEARCH within the last eight years (2018-2025). The total number of participants was 523 mothers of children with autism. Data were analyzed using correlation effect size (correlation coefficient r and sample size N). The effect size value obtained from the random effects model was r = 0.878, p < 0.001. The findings indicate that gratitude and psychological well-being have a strong effect size and are positively correlated. The higher level of gratitude, the higher psychological well-being of mothers in educating children with autism. Mothers with greater psychological well-being are better able to optimally educate and nurture their children with autism, enabling the children to grow and develop across various aspects in accordance with expectations and conditions.